Design, analysis and fabrication of semi-auto cup rinser / Muhammad Amar Zakwan Anuar - Anuar, Muhammad Amar Zakwan (2022)
This report will describe the design, development, and fabrication of a friendly and simple way to wash the cup or other drinking instrument. The concept operation for this project is by using water pressure and scrubbing method to rinse the cups. The main objective to fabricate this project is to develop a simple device that can easily wash many cups, and glass in a short period by implementing two basic concepts washing there it’s scrubbing, and rinsing. The user needs to place the cup onto the spryer and after that to the brush. The project’s material depends on the availability and demand when wants to fabricate. Plastic and steel are the priority material used to make the cup cleaner. The process involved are the drilling, bending, and drawing processes. The SolidWorks software are used to calculate and predict the value of yield stress and factor of safety on the critical part like the drip plate and body part. To sum up, from designing this project, hopefully it may solve one of the house chores problems.